One country, many languages: Exploring a multilingual approach to mathematics teaching and learning in South Africa - (:unkn) unknown (My University, 2018)
The articulation of a multilingual language-in-education policy in South Africa meets many challenges in practice. Research shows that despite what policy says, learners, families and teachers in historically disadvantaged black African schools in the country prefer English as the language of learning and teaching, and maintain the view of African languages as the languages of the home. In this plenary lecture, I comment on a multilingual approach to mathematics teaching and learning that I see as an alternative to constraining language practices in mathematics education. The two main principles of this approach are: the deliberate, proactice and strategic use of the learners' home language and the selection of real life, interesting and high cognitive demand mathematical tasks. The underpinnings are a holistic view of multilingual learners and a notion of language as resource for mathematics teaching and learning.
Keywords: African Research